Preparation of Complexes of 2-[{5-((5-Amino-1,3,4-Thiadiazole-2-yl)Methyl)-1,3,4-Thiadiazole-2-yl-Imino}Methyl]Phenol with Transition Metal Sulphates - Turan, Nevin; Ergin, Zuhal; Sekerci, Memet (Chem Soc Pakistan, 2010)
In the present study 2-[{5-((5-amino-1,3 4-thiadiazole-2-yl)methyl)-1 3 4-thiadiazole-2-ylimino}methyl]phenol (L) has been synthesized by the reaction bis(2-amino-1 3,4-thiadiazolyl)methane and salicylaldehyde The metal complexes of the ligand were prepared with sulfate Co(II) Ni(II) Cu(II) and Zn(II) in DMF as solvent The ligand (L) and its metal complexes have been characterized by elemental analyses IR H-1-NMR spectra, magnetic susceptibility UV-Vis and thermogravimetry-differential thermal analysis (TGA-DTA) The suggested structures for the Zn(II) complex is octahedral for the Ni(II) complex is tetrahedral for the Co(II) complex square-planar and for the Cu(II) complex is square-pyramidal geometry
Keywords: Schiff-Base; Crystal-Structures; Thermal-Behavior; Cu(Ii) Complexes; Co(Ii); Ni(Ii); Mononuclear; Mn(Ii); Derivatives; Copper(Ii)